FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN - Christina, Christina; Salim, Susanto (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research is to identify the effect of financial performance, liquidity, corporate social responsibility, and leverage on firm value. The data used in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2018 - 2020 using Microsoft Excel and Software Eviews version 12. The sample selection technique in this study used purposive sampling and used 15 food and beverage companies. as the research sample. The results of this study indicate that financial performance has a positive and significant effect on firm value. Meanwhile liquidity, corporate social responsibility and leverage have no significant effect on firm value.